2012
DOI: 10.1021/ja301091v
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Stable, Acyclic, Two-Coordinate Silylene

Abstract: The synthesis and characterization of a stable, acyclic two-coordinate silylene, Si(SArMe6 )2 [ArMe6 = C6H3-2,6(C6H2-2,4,6-Me3)2], by reduction of Br2Si(SArMe6 )2 with a magnesium(I) reductant is described. It features a V-shaped silicon coordination with a S–Si–S angle of 90.52(2)° and an average Si–S distance of 2.158(3) Å. Although it reacts readily with an alkyl halide, it does not react with hydrogen under ambient conditions, probably as a result of the ca. 4.3 eV energy difference between the frontier s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(135 citation statements)
references
References 50 publications
5
115
2
5
Order By: Relevance
“…(1) Å in 2) in the free silylenes, 5,6 and the Si-C bond length, 1.829(2) Å, is similar to those in other siliranes.…”
Section: )supporting
confidence: 62%
See 1 more Smart Citation
“…(1) Å in 2) in the free silylenes, 5,6 and the Si-C bond length, 1.829(2) Å, is similar to those in other siliranes.…”
Section: )supporting
confidence: 62%
“…Herein, we report on the first examples of reversible ethylene binding by stable, two-coordinate silylenes. We demonstrate that Si(SAr Me 6 )2 (Ar Me 6 = C6H3-2,6(C6H2-2,4,6-Me3)2), 5 and Si(SAr …”
mentioning
confidence: 73%
“…12,33 We have recently shown that the experimental UV-Vis spectrum of 1 can be interpreted with the help of TD-DFT calculations which showed the first low-energy transition at 382 nm to be of tetrylene n (HOMO)  tetrylene p (LUMO) type. However, as the orbital analysis in Figure 9 demonstrates, the exact bonding characteristics of the frontier orbitals in divalent chalcogenolates depend on the Ch-M-Ch bond angle and no statements on the type of transitions observed in the electronic spectra of 2-16 can therefore be made based on the data available for 1.…”
Section: Electronic Spectramentioning
confidence: 99%
“…Si(SAr Me 6 )2 11 and Si(SAr iPr 4 )2 12 to the alkenes ethylene and norbornadiene, we obtained the silirane compounds (Ar iPr 4 S)2Si(CH2)2 and (Ar Me 6 S)2Si(C7H8). The first species features unique reversible binding to ethylene in toluene solutions with a Gibbs free energy of association (ΔGassn) of −24.9 ± 2.5 kJ mol −1 , 13 a value low enough to be greatly affected by entropic effects.…”
Section: Introductionmentioning
confidence: 99%